1996
DOI: 10.4039/ent128171-2
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECTS OF SELECTED DIETARY SUPPLEMENTS ON SURVIVAL AND REPRODUCTION OF ORIUS INSIDIOSUS (SAY) (HEMIPTERA: ANTHOCORIDAE)

Abstract: Diets combining the eggs of Ephestia kuehniella Zeller (Lepidoptera: Pyralidae) with corn pollen, green snap bean pods, and adult western flower thrips [Frankliniella occidentalis Pergrande (Thysanoptera: Thripidae)] were evaluated for their effects on the predatory anthocorid bug Orius insidiosus (Say). Nymphs fed only corn pollen did not complete development. Fourteen percent of the nymphs fed only green bean pod sections reached the adult stage. Females reared on a diet of bean pod sections did not oviposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
8

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 8 publications
1
24
0
8
Order By: Relevance
“…They also suggested that some nutrition contents in the diet might affect the fecundity of the bug. Many Orius species can be successfully reared on E. kuehniella eggs (Alauzet et al, 1992(Alauzet et al, , 1994Tommasini and Nicoli, 1993;Richards and Schmidt, 1996;Cocuzza et al, 1997;Vacante et al, 1997;Honda et al, 1998;Yano et al, 2002). However, the existence of non-ovipositing females is an important problem from the viewpoint of quality control in the mass-production of Orius species as a biological control agent.…”
Section: Discussionmentioning
confidence: 99%
“…They also suggested that some nutrition contents in the diet might affect the fecundity of the bug. Many Orius species can be successfully reared on E. kuehniella eggs (Alauzet et al, 1992(Alauzet et al, , 1994Tommasini and Nicoli, 1993;Richards and Schmidt, 1996;Cocuzza et al, 1997;Vacante et al, 1997;Honda et al, 1998;Yano et al, 2002). However, the existence of non-ovipositing females is an important problem from the viewpoint of quality control in the mass-production of Orius species as a biological control agent.…”
Section: Discussionmentioning
confidence: 99%
“…As for most predators, the variety and quality of food consumed influences Orius spp. development, reproduction and overall biological performance (Kiman & Yeargan, 1985;Bush et al, 1993;Richard & Schmidt, 1996). Consequently, diet composition is an important consideration in mass-reared cultures of these species.…”
Section: Introductionmentioning
confidence: 99%
“…Resultados semelhantes foram obtidos para ninfas de O. insidiosus alimentadas com F. insularis, cujo período de desenvolvimento foi de 10,4 dias (Rezende 1990) e de 10,8 dias quando alimentadas com F. occidentallis (26°C, 70% UR e 16h de fotofase) (Tommasini & Nicoli 1994). Richards & Schmidt (1996) Os resultados do consumo médio de C. phaseoli por O. insidiosus (Tabela1) assemelharam-se aos obtidos por Rezende (1990) Rezende (1990), isto é, 80,7 ovos, quando o alimento foi F. insularis. Essa fecundidade é superior à encontrada por Tommasini & Bennuzzi (1996), que foi de 65,7 ovos para fêmeas de O. insidiosus alimentadas com F. occidentallis e 20,3 ovos para fêmeas desse predador alimentadas com S. variabilis.…”
Section: Resultsunclassified
“…Alguns autores (Kiman & Yeargan 1985, Richards & Schmidt 1996 Tommasini & Nicoli (1993), que encontraram 17,1 dias para esse predador alimentado com F. occidentalis.…”
Section: Resultsunclassified
See 1 more Smart Citation